The e-Open Sets in Neutrosophic Hypersoft Topological Spaces and Application in Covid-19 Diagnosis using Normalized Hamming Distance - S. Aranganayagi; M. Saraswathi; K. Chitirakala; A. Vadivel (IndoMS, 2023)
In this paper, we introduce a neutrosophic hypersoft e-open set which is the union of neutrosophic hypersoft δ-pre open sets and neutrosophic hypersoft δ-semi open sets in neutrosophic hypersoft topological spaces. Also, we discuss about the relations between neutrosophic hypersoft δ-pre open sets, neutrosophic hypersoft δ-semi open sets, neutrosophic hypersoft e-open sets and neutrosophic hypersoft e∗-open sets and their properties with the examples. Moreover, we investigate some of the basic properties of neutrosophic hypersoft e-interior and e-closure in a neutrosophic hypersoft topological space and proposed some examples for important results. Added to that, an application in Covid-19 diagnosis using normalized Hamming distance via neutrosophic hypersoft sets is discussed.